16S rRNA gene based analysis of Enterobacter sakazakii strains from different sources and development of a PCR assay for identification - Lehner, Angelika (BioMed Central, 2004)
BACKGROUND: E. sakazakii is considered to be an opportunistic pathogen, implicated in food borne diseases causing meningitis or enteritis especially in neonates and infants. Cultural standard identification procedures for E. sakazakii include the observation of yellow pigmentation of colonies and a positive [Image: see text] glucosidase activity. Up to now, only one PCR system based on a single available 16S rRNA gene sequence has been published for E. sakazakii identification. However, in our hands a preliminary evaluation of this system to a number of target and non-target strains showed significant specificity problems of this system. In this study full-length 16S rRNA genes of thirteen E. sakazakii strains from food, environment and human origin as well as the type strain ATCC 51329 were sequenced. Based on this sequence data a new specific PCR system for E. sakazakii was developed and evaluated. RESULTS: By phylogenetic analysis of the new full-length 16S rRNA gene sequence data obtained we could show the presence of a second phylogenetic distinct lineage within the E. sakazakii species. The newly developed 16S rRNA gene targeting PCR system allows identification of E. sakazakii strains from both lineages. The assay's ability to correctly identify different E. sakazakii isolates as well as to differentiate E. sakazakii from other closely related Enterobacteriaceae species and other microorganisms was shown on 75 target and non-target strains. CONCLUSION: By this study we are presenting a specific and reliable PCR identification system, which is able to correctly identify E. sakazakii isolates from both phylogenetic distinct lines within the E. sakazakii species. The impact of this second newly described phylogenetic line within the E. sakazakii species in view of clinical and food safety aspects need further investigation.